Pendekatan Hermeneutika Gadamer Terhadap Kerusakan Ekologi: Analisis Surah Ar-Rum Ayat 41 - Ikhsan Rifki Naswa; Nurul Hamidah; Farhan Suhada (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
of Hans-Georg Gadamer in order to reinterpret the meaning of fasad within the context of the contemporary ecological crisis. The study aims to analyze Surah Ar-Rum verse 41 by emphasizing the dialogical interaction between the horizon of the text and that of the reader in producing an understanding relevant to the present context. Employing library research and hermeneutical analysis, this study situates a dialogue between the horizon of the Qur’anic text of the seventh century and the horizon of modern readers confronted with deforestation, pollution, and climate change. The findings demonstrate that fasād does not merely refer to moral and spiritual corruption but also encompasses ecological destruction resulting from irresponsible exploitation of nature. Through the processes of fusion of horizons and application, the verse underscores humanity’s ethical responsibility as khalifah to cultivate ecological awareness and eco-theological praxis. This study affirms the continued relevance of Qur’anic values in addressing global issues such as environmental degradation. Moreover, Gadamer’s hermeneutical approach provides a methodological framework for understanding religious texts in dynamic and contextual ways and proves effective in bridging classical interpretations with contemporary ecological demands.